Trends in breast cancer incidence among females in Hanoi, 2014-2023, and projections to 2040 - Giang, Nguyen Huong; Ngoc, Luu Minh; Huong, Tran Thi Thanh (Tạp chí Nghiên cứu Y học, 2026)
Breast cancer is the most common cancer among women worldwide and in Vietnam. This study aimed to describe trends in breast cancer incidence among females in Hanoi from 2014 to 2023 and to project the future burden up to 2040. A cross-sectional study with temporal trend analysis was conducted using data from the Hanoi Cancer Registry. Incident cases (ICD-10 code C50) diagnosed between January 1, 2014, and December 31, 2023, were included. Trends were analyzed using Joinpoint regression (version 5.0.2, National Cancer Institute, USA), with a jump model applied to account for potential disruptions during the COVID-19 period. Future cases were projected using a Poisson regression model with population as an offset in Stata version 17.0. A total of 15,646 cases were recorded, with an overall age-standardized incidence rate of 37.77 per 100,000 women. Incidence remained stable from 2014 to 2018, followed by a significant increase from 2018 to 2023. Projections indicate that cases may rise from 1,972 in 2023 to approximately 3,325 by 2040, particularly among women aged ≥50 years old, highlighting the urgent need to strengthen targeted early detection and mammography screening programs for this population.